Pemisahan Penyelenggaraan Pemilu Serentak Tingkat Nasional Dan Daerah - Sri Asriana; Rosmini; Ine Ventyrina (Fakultas Hukum Universitas Mulawarman, 2022)
General election regulations simultaneously raise problems at the level of implementation, because they are considered not to show effectiveness and efficiency in the implementation of general elections in accordance with the purpose of the establishment of these regulations. Therefore, the implementation of the general election regulations simultaneously needs to be reviewed based on the initial objective of issuing the Constitutional Court Decision Number 14/PUU-XI/2013 concerning Simultaneous General Elections, and refers to the implementation of simultaneous general elections in 2019. The research method used in This research is doctrinal, which contains a normative character. There are implications for the implementation of simultaneous elections, it is necessary to construct a law to separate general elections simultaneously at the national and regional levels in 2024 with the implementation of two elections within five years, making it easier for voters to cast their votes, easing the burden on organizers, and optimizing the campaigns of political parties and candidates in the regions. The results of the national elections strengthen the presidential system at the national level, while the results of the regional elections will strengthen local government. Keywords: Election, Simultaneous, Formulation